PARASITIC ROUND WORM - Fatima Sharipovna Nazarova (Journals Park Publishing, 2024)
Nematodes inthe earth on the face of the most numerous cell animals are, of them than 80 000 more types described, the same including 2500 to close the plant is parasitic. Nematodes of stretching, segment microscopic serpent similar round worms are, are they useful or useless to be can.They are in the soil and the plants root in the tissue live. The majority of the soil to be beneficial is that, because to them organic substances breakdown to help will. Nematodes of the species, only a small a part of the parasite is, crops to be harmful if it is, the plant roots with feeding through damage of ywill deliver. Some nematodes in the soil, which live in insect pests attack will and biocontrol of the body as used be can. Other insect parasitic nematodes of pesticides be applied to the can as, tırtıllara topical basis to be applied can.
Keywords: Parasite, fitonematoda, segment, pesticides, ektoparazit, endoparazit, disease, climate, infestatsiya, style asset.